IMPORTANT ASPECTS OF MYASTHENIA GRAVIS (American Journal of Interdisciplinary Research and Development, 2022)
As you know, in all organ systems in the body there are diseases that are inherent in a certain number. The prevention and treatment of these diseases will be the responsibility of young future doctors like us. For example the nerf system.One of the most common cases of disease in this system is : it is associated with the conduction of nerf impulses. In particular , when something iodine affects the body, it is received through receptors located in the impulse skin, tam cognition, sense of smell, hearing, sight and hakozo organs, transmitting it to the brain centers of the head .